Reward, reproducibility and recognition in research – the case for going Open - Kingsley, Danny (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. The advent of the internet has meant that scholarly communication has changed immeasurably over the past two decades but in some ways it has hardly changed at all. The coin in the realm of any research remains the publication of novel results in a high impact journal – despite known issues with the Journal Impact Factor. This elusive goal has led to many problems in the research process: from hyperauthorship to high levels of retractions, reproducibility problems and 'cherry picking' of results. The veracity of the academic record is increasingly being brought into question. An additional problem is this static reward systems binds us to the current publishing regime, preventing any real progress in terms of widespread open access or even adoption of novel publishing opportunities. But there is a possible solution. Increased calls to open research up and provide a greater level of transparency have started to yield practical real solutions. This talk will cover the problems we currently face and describe some of the innovations that might offer a way forward.